Faunistic and ecological accounts on aphids (Homoptera, Aphidoidea) of Southern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Accounts are given on the aphid fauna composition of the two administrative Regions Basilicata and Calabria, in Southern Italian peninsula. In the paper some introductive taxonomic comments deal with local aphidological literature and particularly with a Macchiati's paper (1883-84), where eight new aphid species collected in that territory (Calabria) were described. Thereafter, data of direct field samplings (including host plants and localities) are reported for each aphid species collected in the territory. Here an amount of 402 species, corresponding to about 50% of the Italian aphid fauna as nowdays composed, are checked. Individual data for each of the two Regions, adding a few other records deriving from literature, shown that 314 and 327 species are at present detected in Basilicata and Calabria, respectively. In addition, for a group of eleven species (nine of which are new records for the Italian aphid fauna), more detailed either taxonomic and ecological notes are given.
Keywords: aphids; fauna; Basilicata and Calabria regions; Italy